2005
DOI: 10.1007/s10517-005-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NAD on recovery of adenine nucleotide pool, phosphorylation potential, and stimulation of apoptosis during late period of reperfusion damage to myocardium

Abstract: The system of energy supply in the myocardium of the left and right ventricles did not recover after short-term circulatory disturbances. ATP synthesis decreased in parallel with activation of poly-(ADP-ribose)-polymerase in the ischemic region of the right ventricle, extra-ischemic region, and in the left ventricle by 5.85, 5.4, and 2.2 times, respectively. Intravenous injection of NAD immediately after blood flow resumption in the subacute period of ischemia-reperfusion damage virtually completely normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The results indicated that phenylephrine (PE, 20 µM)-mediated activation of these promoters was significantly reduced by treatment of cells with NAD, thus again demonstrating the anti-hypertrophic potential of NAD [6,19,20]. Early, Sukoyan has shown that treatment with oxidized form of NAD (preparation of Nadcin  ) reversed ischemic-reperfusion injury of myocardium in experimental models [16][17][18] and Bokeria confirm these results in randomized controlled study in patients with unstable angina pectoris and bypass grafting [21]. After this Bruzzone [22], have provided evidence that exogenous NAD enters into cardiomyocytes via connexin 43 (Cx43) channels permeable to extracellular NAD, NAD treatment dramatically decrease astrocytes and neurocytes death induced by a genotoxic agents or ischemic and traumatic damage, markedly decrease autophagy in the brain transient ischemia in experiments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results indicated that phenylephrine (PE, 20 µM)-mediated activation of these promoters was significantly reduced by treatment of cells with NAD, thus again demonstrating the anti-hypertrophic potential of NAD [6,19,20]. Early, Sukoyan has shown that treatment with oxidized form of NAD (preparation of Nadcin  ) reversed ischemic-reperfusion injury of myocardium in experimental models [16][17][18] and Bokeria confirm these results in randomized controlled study in patients with unstable angina pectoris and bypass grafting [21]. After this Bruzzone [22], have provided evidence that exogenous NAD enters into cardiomyocytes via connexin 43 (Cx43) channels permeable to extracellular NAD, NAD treatment dramatically decrease astrocytes and neurocytes death induced by a genotoxic agents or ischemic and traumatic damage, markedly decrease autophagy in the brain transient ischemia in experiments.…”
Section: Discussionmentioning
confidence: 93%
“…The mortality in ISO-treated group was 16% and zero in control group. Twenty seven rabbits with CH were randomly assigned into follows groups relative to receive therapy: CH, control II-without therapy (receive physiological solution, n=10); main I-daily given orally lisinopril (inhibitor of angiotensin converting enzyme, in form of lisinopril-dihydrate, Sigma-Aldrich), 1,0 mg/kg body weight, in combination with nebivolol hydrochloride (a cardioselective beta 1-adrenoceptor blocker facilitating vascular release of nitric oxide (NO), 10 mg/kg per day given orally via gastric lavage for 10 days starting on day 7-th after chronic ISO-induced myocardial damage (n=12); and main II-receive 15 mg/kg body weight, of Nadcin  , first oxidized form NAD-containing drug with antiischemic and anti-inflammatory activities [16][17][18], manufacturing by "Biotechpharm GE", Georgia] (n=11). Treatment duration in both group was 10 days.…”
Section: Experimental Designmentioning
confidence: 99%
“…The presurgery procedures and methods of assessing intracardiac hemodynamics and graduated stenosis of the coronary artery were described elsewhere [1,3]. Assays for ATP and PARP as well as the measurements of NAD/ NADH ratio in cardiomyocytes were performed according to [3,4]. The data were analyzed statistically using SPSS-10 software and Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…Inability of myocardial mitochondria to maintain the NAD/NADH ratio, to produce suffi cient amounts of ATP, and to maintain the water-electrolyte balance triggers the mechanisms of nonapoptotic cell death and the development of necrotic alterations in cardiomyocytes [5]. Consequently, our aim was to examine the possibility of arresting the onset of the processes leading to cardiomyocyte death with adenocine, β-acetyldigoxin, milrinone lactate, and levosimendan (a non-glycoside cardiotonic drug improving myocardial contractility without elevation of intracellular calcium [1][2][3][4]) during chronic HF.…”
mentioning
confidence: 99%
“…The technique of preoperative treatment, study of intracardiac hemodynamics, and method of coronary artery stenosis were described elsewhere [3]. The treated and control animals were killed on day 14 after coronary artery occlusion.…”
Section: Methodsmentioning
confidence: 99%